Development of an IoT-Based Household Solar Power Plant Monitoring and Control System - erradwi, erra; Aan, Aan Febriansyah; Tri, Tri Agusti Farma (STMIK KHARISMA Makassar, 2026)
Solar Power Generation System (PLTS) for households equipped with an Internet of Things (IoT)-based control system is designed to improve efficiency and ease of energy usage monitoring. The research methods include the design of a household-scale solar power system, the integration of sensors for monitoring electrical parameters and environmental conditions, as well as the development of an IoT application for real-time control and monitoring. Data were collected through system testing on a household-scale simulation with variations in load and weather conditions.